Factors contributing to inaccurate diagnosis code in obstetric case in hospital - Alfina Aisatus Saadah; Risma Nur Sukmawati (Science Midwifery, 2023)
As the diagnostic code serves as the foundation for determining the cost of health services and formulating policy, its quality must be ensured. In some hospitals, the code is extremely inaccurate. If the patient's diagnosis code is not accurately coded, the level of data validation for the obtained information will be low. This will result in inaccurate reports, including outpatient morbidity reports, top ten disease reports, and Health Insurance (Jamkesmas) claims. This study aimed to examine the inaccuracy of the diagnostic code for obstetric cases in hospital. This study employs a Literature review methodology in which researchers will compile various scientific articles/journals into a scientific work. Based on the findings of the study, the percentage of inaccurate diagnosis codes for obstetric cases was greater than 50% in five journals, 50% in one journal, and less than 50% in three journals. The inaccuracy of the obstetric case diagnosis code is due to Man, Machine, Material, and Method factors. Thereby, it can be concluded that the percentage of inaccuracy of the diagnostic code for obstetric cases is quite high, and that the most common factor causing inaccuracy of the diagnostic code for obstetric cases is the Man factor, namely that the writing of the diagnosis is less clear, complete, and specific. Consequently, it is necessary to monitor and reevaluate medical officers, especially doctors and assistants, and to establish a policy stating that writing diagnoses is the responsibility of doctors and must adhere to ICD rules.